STRATEGIES FOR STRENGTHENING THE GLOBAL COMPETITIVENESS OF INDONESIAN CULINARY FOOD FROM THE PERSPECTIVE OF CREATIVE ECONOMIC MANAGEMENT - Frangky Silitonga; Hendra Syaiful; Tri Muntia Yusri; Heri Nuryanto; Karium Jackson M Nainggolan; Widyo Wicaksono; Kintan Sabrina (JURNAL MANAJEMEN KULINER, 2026)
Indonesian cuisine is a leading subsector within the creative economy with significant potential as a global competitiveness instrument and cultural diplomacy tool. This study aims to analyze the feasibility of Indonesian cuisine gaining global recognition from a strategic management and creative economy perspective. The method used is a descriptive-analytical approach with literature review and secondary data analysis from Statistics Indonesia (BPS) and national creative economy reports. The findings indicate that the culinary subsector contributes approximately 40% to the creative economy GDP, while Indonesia’s processed food exports reached more than USD 41 billion in 2023. Global recognition of dishes such as Rendang, Nasi Goreng, and Sate strengthens Indonesia’s gastronomic diplomacy position. The study implies the necessity of national branding strategies, quality standardization, and competitive market expansion to enhance global competitiveness.